2021
DOI: 10.1002/tcr.202100061
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Construction and Functionalizations of Nitrogen‐Containing Heterocycles Through Migratory Insertion of Metal‐Carbenes/Nitrenes

Abstract: Nitrogen-containing heterocycles are widely found in various biologically active substrates, pharmaceuticals, natural products and organic materials. Consequently, the continuous effort has been devoted towards the development of straightforward, economical, environmentally acceptable, efficient and ingenious methods for the synthesis of various Ncontaining heterocycles and their functionalizations. Arguably, one of the most prominent direct strategy is regioselective CÀ H bond functionalizations which provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Due to the leading contributions by Davies, 24–26 Doyle, 4,6 Wang, 7,27 Fox, 28 and others, important advances have recently been achieved, some of which were highlighted, 11,29–31 and commented in prospects, 32–35 book chapters, 36,37 books, 38,39 and personal accounts. 24–28,40–43 In the recent reviews regarding C–H functionalization and diazo compounds, carbene insertion to C–H bonds is usually composed as an important section. For example, fragmentary summary was made in the following reviews: transition-metal-catalyzed cross-coupling through carbene migratory insertion, 7,8 C–H functionalization via iron-catalyzed carbene transfer (insertion) and other reactions, 9,10,44,45 transition-metal-catalyzed insertion reactions with donor/donor carbenes, 23 Co( iii ), Rh( iii ), and Ir( iii )-catalyzed direct C–H alkylation/alkenylation/arylation with carbene precursors, 46 palladium-catalyzed bridging C–H activation by using alkenes, alkynes, and diazo compounds, 47 Tp x M-catalyzed (Tp x = scorpionate ligand, M = Cu, Ag, Au) C(sp 3 )–H bond functionalization, 48–50 photocatalytic reactions with diazo compounds, 51 metal-carbene mediated alkylation of unactivated C(sp 3 )–H bond, 52 gold-catalyzed transformations of α-diazocarbonyl compounds 53 and C–H activation processes, 54 catalytic C–H functionalization by metal carbene and nitrene insertion 55 and related dirhodium complexes, 56,57 and direct C(sp 3 )–H bond activation adjacent to nitrogen in heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the leading contributions by Davies, 24–26 Doyle, 4,6 Wang, 7,27 Fox, 28 and others, important advances have recently been achieved, some of which were highlighted, 11,29–31 and commented in prospects, 32–35 book chapters, 36,37 books, 38,39 and personal accounts. 24–28,40–43 In the recent reviews regarding C–H functionalization and diazo compounds, carbene insertion to C–H bonds is usually composed as an important section. For example, fragmentary summary was made in the following reviews: transition-metal-catalyzed cross-coupling through carbene migratory insertion, 7,8 C–H functionalization via iron-catalyzed carbene transfer (insertion) and other reactions, 9,10,44,45 transition-metal-catalyzed insertion reactions with donor/donor carbenes, 23 Co( iii ), Rh( iii ), and Ir( iii )-catalyzed direct C–H alkylation/alkenylation/arylation with carbene precursors, 46 palladium-catalyzed bridging C–H activation by using alkenes, alkynes, and diazo compounds, 47 Tp x M-catalyzed (Tp x = scorpionate ligand, M = Cu, Ag, Au) C(sp 3 )–H bond functionalization, 48–50 photocatalytic reactions with diazo compounds, 51 metal-carbene mediated alkylation of unactivated C(sp 3 )–H bond, 52 gold-catalyzed transformations of α-diazocarbonyl compounds 53 and C–H activation processes, 54 catalytic C–H functionalization by metal carbene and nitrene insertion 55 and related dirhodium complexes, 56,57 and direct C(sp 3 )–H bond activation adjacent to nitrogen in heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…2-Alkenylanilines are versatile synthetic intermediates frequently used in the synthesis of indoles, , quinolones, , indazoles, benzo­[ b ]­azepines, benzoxazinones, and so forth. In the meantime, metal carbenes generated from diazo compounds through extrusion of N 2 have played an important part in modern synthetic chemistry . In particular, carbenes generated from diazonaphthalen-2­(1 H )-ones (DZNPs) have been used for introducing a naphthol moiety via transition metal-catalyzed and directing group (DG)-guided inert chemical bond functionalization. , For examples, Lee et al have reported the construction of 3-naphthylindole via Rh­(II)-catalyzed arylation of indoles with DZNPs .…”
Section: Introductionmentioning
confidence: 99%
“…Recently C–H bond functionalization based on the migratory insertion of metal carbenes has become an important area in synthetic chemistry . Considering our recent work on migratory-insertion-based C–H bond functionalizations, especially using quinoid carbenes, we hypothesized that the introduction of a naphthol moiety into the C1-position of isoquinolines and congeners via this strategy might lead to our desired heterobiaryls. Herein we report an earth-abundant, cheap, Cu­(II)-catalyzed simple and direct construction of QUINOX and related heterobiaryls using quinoid-carbene, which further extends to known related P,N ligands (Scheme iii).…”
mentioning
confidence: 99%